Characteristics and transmission dynamics of COVID-19 in healthcare workers at a London teaching hospital. Issue 2 (October 2020) - Zheng, C.; Hafezi-Bakhtiari, N.; Cooper, V.; Davidson, H.; Habibi, M.; Riley, P.; Breathnach, A.
Summary: Background: Healthcare worker (HCW)-associated coronavirus disease 2019 (COVID-19) is of global concern due to the potential for nosocomial spread and depletion of staff numbers. However, the literature on transmission routes and risk factors for COVID-19 in HCWs is limited. Aim: To examine the characteristics and transmission dynamics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in HCWs in a university teaching hospital in London, UK. Methods: Staff records and virology testing results were combined to identify staff sickness and COVID-19 rates from March to April 2020. Comparisons were made with staff professional groups, department of work, and ethnicity. Findings: COVID-19 rates in our HCWs largely rose and declined in parallel with the number of community cases. White and non-White ethnic groups among our HCWs had similar rates of infection. Clinical staff had a higher rate of laboratory-confirmed COVID-19 than non-clinical staff, but total sickness rates were similar. Doctors had the highest rate of infection, but took the fewest sickness days. Critical care had lower rates than the emergency department (ED), but rates in the ED declined when all staff were advised to use personal protective equipment (PPE). Conclusion: Sustained transmission of SARS-CoV-2 among our hospital staff did not occur, beyond the community outbreak, even in the absence of strict infection control measures in non-clinical areas. Current PPE appears to be effective when used appropriately. Our findings emphasize the importance of testing both clinical and non-clinical staff groups during a pandemic.